A critical analysis of the de-peasantisation process in Nepal with specific reference to the role of state land policies since the 1950s - Basnet, Jagat (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
The principal objective of this thesis is to offer a critical analysis of the process of de-peasantisation in Nepal since 1950, with a particular focus on the capitalist neo-liberal restructuring of the economy beginning in the early 1990s. The analysis begins by tracing the legacy of feudal land practices and landholdings from the pre-1950 Rana and Shah dynasties. It was under these feudal dynasties that economic and political institutions of extraction first emerged, leading to a landlord-peasant agrarian economy in which peasants (often as tenants/sharecroppers and smallholders) were subordinate to the power nexus between feudal landlords and the ruling dynasties. After 1950, a window of democratic opening was soon interrupted by the formation of the party-less Panchayat system, which lasted from 1960 to 1990. In 1964, a major land reform measure was enacted under the Lands Act, with the goal of enhancing the security and livelihood of the peasantry. However, this process was met with significant resistance by feudal landlords, and actually led to deepening insecurity and the loss of land by peasants, with farmers belonging to lower castes and indigenous groups experiencing this with a greater degree of intensity. The overall result of this period was the beginnings of what is referred to in this study as de-peasantisation. This line of analysis shows that the institutions of extraction remained firmly in place even after the reforms of this period. Finally, the neo-liberal period, which was marked by land titling, the marketisation of land, and the commercialisation of agriculture, represents the late entry of capitalism into Nepal. This period saw the deepening and widening of the process of de-peasantisation, including further loss of peasants' access to land and a general turn to wage-labour. In this regard, despite propagating the slogan 'land to the tillers', the major political parties in Nepal (including the Maoist party) have failed to defend the interests of the peasantry. Some progressive civil society groups have recently sought to do better, but there is also evidence of peasant organisations themselves seeking to resist and oppose the de-peasantisation effects of neo-liberal restructuring. This thesis thus considers the form and extent of de-peasantisation in Nepal, and some responses to it, over an extended period. A broad Marxist-based political economy perspective has been adopted in pursuing the principal thesis objective, but one which argues that there is a symbiotic relationship between economic and political power, such that the latter is not reducible to the former. The thesis draws upon original fieldwork in twenty districts of Nepal, including through the use of a survey, interviews, observations, case studies, and focus group discussions, thus combining both quantitative and qualitative research methods. Based on this fieldwork, it becomes clear that (i) there are major social, economic, and political forces behind the processes of de-peasantisation in the studied districts (and in Nepal more broadly), and that (ii) the Nepali peasantry is becoming increasingly landless, or land-short, and subject to processes of proletarianisation.
Keywords: Land tenure -- Nepal; Land reform -- Law and legislation -- Nepal; Nepal -- Politics and government; Peasants -- Nepal -- Economic conditions; Panchayat -- Nepal